Spatial-Temporal Distribution of Prorocentrum concavum Population in Relation to Environmental Factors in Xincun Bay, a Tropical Coastal Lagoon in China - Zou, Jian; Xie, Hang; Zheng, Chengzhi; Lu, Songhui (Frontiers in Marine Science, 2022)
A harmful benthic Prorocentrum concavum bloom was recorded in August 2018 in Xincun Bay, China, which is the location of a national seagrass nature reserve. Annual ecological surveys have been conducted to study the population dynamics of P. concavum in the benthic community and water column. Seasonal variations in benthic P. concavum abundance were found and the abundances on seagrass and macroalgae in the wet season were 2.5 and 2.82 times higher, respectively, than those in the dry season, although the differences were not statistically significant. The abundance of P. concavum in the water column differed significantly between seasons. The maximum abundances of benthic and planktonic P. concavum were (1.7 ± 0.59) × 106 cells (100 cm2)−1 on Thalassia hemperichii in July and 2.0 × 104 ± 4.7 × 103 cells L−1 in June, respectively. High spatial heterogeneity in P. concavum abundance was observed among five sampling sites. Abundances were significantly higher in seagrass beds than those in macroalgae beds, mangroves, and coral reefs. The abundance of P. concavum at site A (in a seagrass bed and close to a cage-culture area) was 5.6 times higher than that at site D (seagrass bed and distant from the cage-culture area). Planktonic P. concavum showed a similar spatial distribution and presented a maximum density at site A. Moreover, the abundance of benthic P. concavum also showed heterogeneity on host substrates, and the abundance on T. hemperichii was significantly higher than that on sediment. Based on a Spearman’s test, temperature, dissolved organic phosphorus, and dissolved organic nitrogen were the three important factors driving the spatiotemporal distribution of benthic P. concavum in Xincun Bay. Planktonic P. concavum were derived from cells on the substrates and were influenced by concentrations of dissolved oxygen. In conclusion, seagrass beds may be a reservoir of harmful benthic algal blooms in Xincun Bay and the dense cage-culture area provides sufficient organic nutrients for the growth and reproduction of benthic dinoflagellates.